Keefektifan Vidio Animasi Berbantuan Media Wordwall Terhadap Materi Ilmu Pengetahuan Alam untuk Meningkatkan Motivasi dan Hasil Belajar Siswa: Penelitian - Gina Amelia; Arif Widiyatmoko; Langlang Handayani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the effectiveness of using animated videos assisted by Wordwall in improving students' motivation and learning outcomes on the material of characteristics of living things. The type of research used is quantitative research with True Experimental Design type Pretest Posttest Control Design. The population in this study were grade III students of Gunungsugih 02 Elementary School as the experimental class and Ganggawang Elementary School as the control class with a total of 56 students. The instruments used included tests and questionnaires to measure learning motivation. Data analysis techniques used normality tests, homogeneity tests, and T tests. The results of the study showed that science learning using animated video media assisted by Wordwall had a positive effect on students' motivation and learning outcomes. The average post-test score of the experimental class was 73, while the control class was 42.96. In addition, the results of the post-questionnaire showed that the average motivation score of students in the experimental class (61.41) was higher than the control class (51). The T-test showed a significant difference between the pre-questionnaire and post-questionnaire in the experimental class, with Tcount (2.30) greater than Ttable (2.03). This indicates that the use of animated video media assisted by Wordwall has a positive effect on increasing student motivation and learning outcomes in science material.